Influence of ground load on adjacent oil and natural gas pipelines - Zhengwei Guo; Yinchun Gong (Advances in Mechanical Engineering)
The foundation soil will move under the action of ground building, which generates large additional stress on burial pipeline. If the stress exceeds the yield strength of pipeline, the pipeline will be destroyed. In order to analyze the influence of ground building on buried pipelines, theoretical and numerical method are used to analysis stress and deformation of pipeline. The research results show that ground building has a significant impact on the adjacent soil. The softer the soil is, the greater the internal stress within the soil will be. The effects of distance between pipeline and ground building on stress and deformation of pipelines are researched, and stress and deformation of pipelines subjected to the moving ground building are investigated. The analysis results have deeply understanding of ground building on the adjacent pipelines, and it has guiding significance for the construction of pipelines.